Congenital nephrotic syndrome with a novel NPHS1 mutation. Issue 11 (November 2016) - Yoshizawa, Chikage; Kobayashi, Yasuko; Ikeuchi, Yuka; Tashiro, Masahiko; Kakegawa, Satoko; Watanabe, Toshio; Goto, Yoshimitsu; Nakanishi, Koichi; Yoshikawa, Norishige; Arakawa, Hirokazu
Abstract: Congenital nephrotic syndrome of the Finnish type (CNF) is a rare autosomal recessive disorder. The incidence of CNF is relatively high in Finland but considerably lower in other countries. We encountered a male newborn with CNF, associated with compound heterozygous mutations in nephrosis 1, congenital, Finnish type ( NPHS1 ). The patient was admitted to hospital as a preterm infant. Physical and laboratory findings fulfilled the diagnostic criteria of nephrotic syndrome, and were compatible with a diagnosis of CNF, but there was no family history of the disease. On genetic analysis of NPHS1 a paternally derived heterozygous frame‐shift mutation caused by an 8 bp deletion, resulting in a stop codon in exon 16 (c.2156‐2163 delTGCACTGC causing p.L719DfsX4), and a novel, maternally derived nonsense mutation in exon 15 (c.1978G>T causing p.E660X) were identified. Early genetic diagnosis of CNF is important for proper clinical management and appropriate genetic counseling.